2000
DOI: 10.1128/mcb.20.1.113-125.2000
|View full text |Cite
|
Sign up to set email alerts
|

Alleviation of Human Papillomavirus E2-Mediated Transcriptional Repression via Formation of a TATA Binding Protein (or TFIID)-TFIIB-RNA Polymerase II-TFIIF Preinitiation Complex

Abstract: Transcription in human papillomaviruses (HPVs) is mainly regulated by cellular transcription factors and virus-encoded E2 proteins that act as sequence-specific DNA-binding proteins. Although the functions of E2 as a transcriptional activator and a repressor have been well documented, the role of cellular factors involved in E2-mediated regulation of the HPV promoters and the mechanism by which E2 modulates viral gene expression remain unclear. Using reconstituted cell-free transcription systems, we found that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
49
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 45 publications
(56 citation statements)
references
References 68 publications
(73 reference statements)
7
49
0
Order By: Relevance
“…4D, lanes 1-12), a conclusion further supported by the pairwise mutational studies (Fig. 4D, lanes 13-24) and also by previous in vivo and in vitro assays (Hou et al 2000 and references therein).…”
Section: E2-p5 Complex-mediated Silencing Of Ap-1-dependent Hpv Chrosupporting
confidence: 67%
See 4 more Smart Citations
“…4D, lanes 1-12), a conclusion further supported by the pairwise mutational studies (Fig. 4D, lanes 13-24) and also by previous in vivo and in vitro assays (Hou et al 2000 and references therein).…”
Section: E2-p5 Complex-mediated Silencing Of Ap-1-dependent Hpv Chrosupporting
confidence: 67%
“…2A). We have previously shown that transcription in vitro from this HPV-11 URR-driven DNA template initiates at the correct start site and faithfully recapitulates E2-mediated regulation of E6 promoter activity as observed in vivo (Hou et al 2000). This HPV-11 DNA template was assembled into chromatin by incubating with purified HeLa core histones, Drosophila nucleosome assembly factor ACF (a protein dimer reconstituted from recombinant Acf1 and FLAG-tagged ISWI), and recombinant human NAP-1 histone chaperone (Fig.…”
Section: E2-p5 Is a Transcriptional Silencing Complex Capable Of Inhmentioning
confidence: 99%
See 3 more Smart Citations